Inside the coordination paradigm: new perspectives on minority presidents and coalition management - Chaisty, P; Cheeseman, N; Power, TJ (Oxford University Press, 2020)
In this chapter, we examine the shift in presidentialism studies away from Linzian questions of conflict towards questions of coordination in executive-legislative relations. This change of focus has brought presidential studies into line with the research on parliamentary systems, generating a more unified literature on comparative executive politics. Focusing specifically on minority presidents and issues of coalition management, we explore how a conceptual vocabulary familiar to students of parliamentarism has shaped the emerging research agenda. We consider the phenomenon of ‘coalitional presidentialism’, which has become the modal form of minority presidential rule in modern democracies facing higher levels of party fragmentation. We discuss why coalitional presidentialism ‘matters’ for both empirical and theoretical reasons, and review the state of the literature on coalition management. Finally, we identify areas of future research in this field.